Pengembangan Sistem Informasi Untuk Menentukan Prioritas Pemberian Kredit dengan Metode Promethee - Sujarwo, Sujarwo (Universitas Diponegoro, 2015)
This study develops an information system for decision-making on priority lending and introduce new information into the decision-making process resulting in the selection process more realistic.The method used in this research method PROMETHEE